Acute Kidney Injury Associated with Severe Leptospirosis: Fatal Re-Emerging Disease in Latin America - Elber Osorio-Rodríguez; Dairo Rodelo-Barrios; Carlos Rebolledo-Maldonado; Alberto Polo-Barranco; Jhonny Patiño-Patiño; Mauricio Aldana-Roa; Valeria Sánchez-Daza; Emily Sierra-Ordoñez; Alfonso Bettin-Martínez (MDPI AG, 2024)
Leptospirosis is a re-emerging zoonotic disease that has had an unprecedented impact on most health systems in the world. The spectrum of symptoms is variable and usually ranges from asymptomatic cases to severe manifestations involving multiple organ dysfunction accompanied by jaundice, hemorrhage, meningitis, and acute kidney injury that requires the need for intensive care assistance. Although early antibiotic treatment is usually effective, in severe cases, it may require renal replacement therapy, invasive mechanical ventilation, vasoactive support, and invasive hemodynamic monitoring, increasing the risk of death. In Latin America, the real burden of acute kidney injury in this condition is unknown and may be underestimated due to the rapid progression of the disease, similar to other vector zoonoses, and the low coverage of diagnostic tests in primary care, especially in rural regions. Therefore, below, we review the clinical aspects and describe the scientific, clinical, and therapeutic evidence of acute kidney injury attributed to Leptospira spp. and its relevance in patients with severe leptospirosis in Latin America.